2017
DOI: 10.5897/ajb2017.16073
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of color and increase in anthocyanin content of Niagara Rosada grapes with application of abscisic acid

Abstract: This study aimed to assess the application effect of abscisic acid (S-ABA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…Color quality analysis for both seasons suggests that lightness values among all the grapes decreased over time, starting from V until harvest (Table 3). However, it has been confirmed that the two applications of S-ABA at different timings of V significantly decrease L* values (Tecchio et al, 2017).…”
Section: Lightness (L*) Chroma (C*) and Hue Angle (H°) Of Berriesmentioning
confidence: 88%
See 3 more Smart Citations
“…Color quality analysis for both seasons suggests that lightness values among all the grapes decreased over time, starting from V until harvest (Table 3). However, it has been confirmed that the two applications of S-ABA at different timings of V significantly decrease L* values (Tecchio et al, 2017).…”
Section: Lightness (L*) Chroma (C*) and Hue Angle (H°) Of Berriesmentioning
confidence: 88%
“…However, this slight change in color purity is undetectable to the naked eye and has no negative effect on the market value of the grapes (Olivares et al, 2017). Some studies have reported S-ABA has no effect on h° (Yamamoto et al, 2015;Tecchio et al, 2017). However, in 2015 season, the h°decreased along with L* (Table 3), implying a diversion from the green towards red color (Olivares et al, 2017).…”
Section: Lightness (L*) Chroma (C*) and Hue Angle (H°) Of Berriesmentioning
confidence: 94%
See 2 more Smart Citations
“…In different red grape cultivars, ABA treatments induced also a more rapid coloring of the berry skin anticipating harvest and increasing the amount of marketable yield, without negative effects on sugar and acid content [9,14]. Some cultivars, such as "Crimson Seedless", need just one application of ABA [10], but others like "Niagara Rosada" and "Rubí" require several applications [15,16]. In warm areas, two applications of ABA are often needed [2].…”
Section: Introductionmentioning
confidence: 99%